Effects of postural threat on perceptions of lower leg somatosensory stimuli during standing - Cleworth, Taylor W.; Peters, Ryan M.; Chua, Romeo; Inglis, J. Timothy; Carpenter, Mark G. (Frontiers in Neuroscience, 2023)
Height-induced postural threat affects emotional state and standing balance behaviour during static, voluntary, and dynamic tasks. Facing a threat to balance also affects sensory and cortical processes during balance tasks. As sensory and cognitive functions are crucial in forming perceptions of movement, balance-related changes during threatening conditions might be associated with changes in conscious perceptions. Therefore, the purpose of this study was to examine the changes and potential mechanisms underlying conscious perceptions of balance-relevant information during height-induced postural threat. A combination of three experimental procedures utilized height-induced postural threat to manipulate emotional state, balance behavior, and/or conscious perceptions of balance-related stimuli. Experiment 1 assessed conscious perception of foot position during stance. During continuous antero-posterior pseudorandom support surface rotations, perceived foot movement was larger while actual foot movement did not change in the High (3.2 m, at the edge) compared to Low (1.1 m, away from edge) height conditions. Experiment 2 and 3 assessed somatosensory perceptual thresholds during upright stance. Perceptual thresholds for ankle rotations were elevated while foot sole vibrations thresholds remained unchanged in the High compared to Low condition. This study furthers our understanding of the relationship between emotional state, sensory perception, and balance performance. While threat can influence the perceived amplitude of above threshold ankle rotations, there is a reduction in the sensitivity of an ankle rotation without any change to foot sole sensitivity. These results highlight the effect of postural threat on neurophysiological and cognitive components of balance control and provide insight into balance assessment and intervention.